The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1128/mcb.00474-16
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Linear Ubiquitin Chain Assembly Complex by Caspase-Mediated Cleavage of RNF31

Abstract: Cell death and survival signaling pathways have opposed but fundamental functions for various cellular processes and maintain cell homeostasis through cross talk. Here we report a novel mechanism of interaction between these two pathways through the cleavage of RNF31 by caspases. RNF31, a component of the linear ubiquitin chain assembly complex (LUBAC), regulates cell survival by inducing linear ubiquitination of NF-B signaling components. We found that RNF31 is cleaved under apoptosis conditions through vario… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 24 publications
(30 reference statements)
0
16
0
Order By: Relevance
“…Conversely, the shorter N‐terminal fragment was still visible in cells mutated for D387A (Fig E). Another study recently described that HOIP is cleaved at D390, in addition to D348 and D387 upon TNF stimulation (Joo et al , ). In accordance, HOIP D348A/D387A/D390A (HOIP AAA ) is completely resistant to TRAIL‐induced cleavage (Fig E).…”
Section: Resultsmentioning
confidence: 99%
“…Conversely, the shorter N‐terminal fragment was still visible in cells mutated for D387A (Fig E). Another study recently described that HOIP is cleaved at D390, in addition to D348 and D387 upon TNF stimulation (Joo et al , ). In accordance, HOIP D348A/D387A/D390A (HOIP AAA ) is completely resistant to TRAIL‐induced cleavage (Fig E).…”
Section: Resultsmentioning
confidence: 99%
“…Labeling of DUBs using HA-Ub-Vs showed that at least 4-5 DUBs were consistently suppressed or inhibited by TRAIL in sensitive cells. This labeling can only recognize USP (ubiquitin specific protease) family members, and thus TRAIL may also affect other ubiquitin and DUB family proteins including E1, E2 and E3 ligases; in fact, cleavage of the E3 ligase RNF31 was shown to be TRAIL dependent [30]. The few DUBs inhibited by TRAIL may not be direct targets and should be further investigated.…”
Section: Discussionmentioning
confidence: 99%
“…However, under conditions where the expression of NF-κB-target genes is suppressed, such as by the protein synthesis inhibitor cycloheximide, TNF-α stimulation extensively induces apoptosis through the generation of TNFR complex IIa, which is composed of RIP1, FADD, and caspase 8 [55] (Figure 2). Subsequently, caspase 8 activates caspase 3 to induce extrinsic apoptosis, and the activated caspases cleave the N-terminal portion of HOIP [39,56]. A genetic deficiency of LUBAC subunits causes reduced expression of NF-κB genes, and thus efficiently induces TNF-α-mediated apoptosis in mice [11][12][13]38,57].…”
Section: Lubac-mediated Regulation Of Cell Deathmentioning
confidence: 99%